East-West trade and the technology gap: a political and economic appraisal - Wasowski, Stanislaw; Institute for Defense Analyses (New York : Praeger, 1970)
The papers provided useful insights into the continuing problems of East-West relations, especially as they relate to trade and as they are projected against the background of the wide technology gap between Eastern Europe and the West.
"A conference ... held in October 1968 under the sponsorship of the International and Social Studies Division of the Institute for Defense Analyses."
Includes bibliographical references.
rpm 21/01/2018
Loans
Keywords: East-West trade; Technology transfer